19 Overall survival after surgical staging by lymph node dissection versus sentinel lymph node biopsy in endometrial cancer: a national cancer database study. (13th November 2020) - Garzon, S; Mariani, A; Day, C; Habermann, EB; Langstraat, CL; Glaser, GE; Kumar, A; Larish, A
Abstract : Objectives: To investigate the association between the type of lymph node (LN) assessment and overall survival (OS) in endometrial cancer (EC). Methods: Patients with stage I-III EC who underwent a hysterectomy and LN assessment from 2012 to 2015 were identified from the National Cancer Database. Multivariable Cox proportional hazards regression analysis was performed to assess factors associated with OS. Results: Of 68, 614 patients identified, 64, 796 underwent lymphadenectomy (LND) only, 1, 777 sentinel lymph node biopsy only (SLN-B), and 2, 041 both procedures (SLN-B/LND). On multivariable analysis, SLN-B and SLN-B/LND were not associated with different OS compared to LND (hazard ratio [HR]: 0.92; 95%CI: 0.73–1.17 - HR: 0.91; 95%CI: 0.77–1.07, respectively). Similarly, when stratified by LN status, SLN-B and SLN-B/LND reported similar OS compared to LND, both in negative (HR: 1.03; 95%CI: 0.85–1.26 – HR :0.95; 95%CI: 0.73–1.23, respectively) and positive (HR: 0.92; 95%CI: 0.55–1.54 – HR: 0.76; 95%CI: 0.57–1.03, respectively) LNs. Including only LND with ≥10 pelvic and ≥1 para-aortic LNs removed, no difference in OS was observed between LND and SLN-B or SLN-B/LND in the entire cohort, and in negative or positive LNs. In all analyses, older age, Charlson-Deyo Score ≥2, black race, higher American Joint Committee on Cancer (AJCC) pathologic T stage, grade 3, presence of lymphovascular infiltration, type-2 histology, and absence of chemotherapy or radiation therapy were independently associated with worse OS. Conclusions: When compared to SLN-B or SLN-B/LND, LND does not appear to improve OS in EC, even in the presence of LN metastases.